Michel Foucault y la literatura Teoría, vida, política - Blanco, Azucena G. (De Gruyter, 2023)
This collected volume explores Foucault's literary thought, in light of the recent publication of unpublished works from his first period (1960s-1970s). It aims at establishing an archeology of the texts that Foucault devotes to literary theory and to clearly literary concepts such as fiction, outside (Blanchot) or transgression (Bataille), in order to relate them to key concepts of the second Foucault (parresia, self-care, veridiction).